2012
DOI: 10.5539/elt.v5n4p161
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Foreign Language Learning on Creativity

Abstract: The present study investigates the possible influence of foreign language learning on individuals' divergent thinking abilities. Unlike the large body of research devoted to unfolding the effect of bilingualism on cognitive functions, foreign language learning has gained little attention. This study aimed at bringing into attention the distinctive nature of foreign language learning which deserves a separate line of investigation. To this end, controlling age, gender, socioeconomic status, and previous learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 23 publications
4
39
0
1
Order By: Relevance
“…He argued that "Poetry gives students a creative way to construct and express their ideas, and it gives teachers a new way to listen" (p.789). In another study, Ghonsooly, Shoqi (2012) investigated the effect of foreign language learning on individuals' divergent thinking abilities. Their results showed that "learning English as a foreign language to an advanced level significantly enhances all four divergent thinking abilities, i.e., fluency, elaboration, originality and flexibility".…”
Section: Review Of Literature Creativitymentioning
confidence: 99%
“…He argued that "Poetry gives students a creative way to construct and express their ideas, and it gives teachers a new way to listen" (p.789). In another study, Ghonsooly, Shoqi (2012) investigated the effect of foreign language learning on individuals' divergent thinking abilities. Their results showed that "learning English as a foreign language to an advanced level significantly enhances all four divergent thinking abilities, i.e., fluency, elaboration, originality and flexibility".…”
Section: Review Of Literature Creativitymentioning
confidence: 99%
“…It has roots in the quantitative ex post facto research study that Sehic (2016) conducted and the research studies that Ghonsooly and Showqi (2012), Hajilou et al (2012), and Pishghadam et al (2011) conducted. The literature review revealed a significant body of research studies that investigated link(s) between the second language learning and cognitive skills and a very limited number of studies that investigated the relationships between English language learning and creative thinking skills.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the purpose of this sequential explanatory mixed-methods case study is to investigate whether a group of seven newly arrived immigrants in the United States who were enrolled in ESL classes at a community college in the northeastern United States will have better posttest than pretest performance in the domains of fluency, flexibility, originality, and elaboration as measured using the Alternate Uses Test and to build on existing research studies on this topic (Ghonsooly & Showqi, 2012;Kharkhurin, 2010;Pishghadam et al, 2011;Sehic, 2016). HA1: ESL learners and monolingual individuals in this mixed-methods case study will score significantly differently in terms of fluency, flexibility, originality, and elaboration as measured with the Alternate Uses Test.…”
Section: Introductionmentioning
confidence: 99%
“…Others have noted a strong tradition in African Americans of cognitive flexibility, imagination, and open‐mindedness . It is also worth noting that bilinguals have been shown to outperform monolinguals on creativity tasks . Indeed, a multilingual environment has been shown to increase perspective‐taking (which is related to openness to experience) in infants …”
Section: Bias Creativity and Intelligencementioning
confidence: 99%